Credit-using behavior of Muslims in non-Muslim country:A study of Nakhon Si Thammarat, Thailand - Pornpen Thippayana; Nalinee Thinnam (Cogent Business & Management, 2023)
In today's globalizing economy, a wide variety of credit sources are available to people in need of funds. However, for Muslims, prescriptions and limitations imposed by the Islamic religion have the potential to shape their credit-seeking behavior. This study investigates credit-using behavior of Muslims in Thailand, a non-Muslim country. The sample comprised 385 Muslims selected from 13 districts in Nakhon Si Thammarat. Data were obtained through face-to-face administration of structured questionnaires and analyzed through means, frequencies, standard deviation and ANOVA. Findings showed that most of the Muslims in Nakhon Si Thammarat did not seek credit from Islamic sources. Instead, they looked to conventional banks, General Cooperative and Saving Group and Non-bank creditors. In addition, most Muslim credit users were found to be conservative, had only one credit contract with one financial institution, minimal remaining debt balances, and were punctual in debt repayment. It was also revealed that Islamic Cooperatives and Savings groups constituted the most suitable Islamic source of funds for Shariah-compliant credit. It is recommended that stakeholders in the banking and credit sector should put in more effort to advance the operations of Islamic cooperatives and savings groups to provide convenient access to financial services and broaden the scope of Islamic credit to Muslims.
Keywords: 650; Credit-using behavior; Islamic credit; Muslim; non-Muslim country; Shariah principle; Thailand